Pengembangan KOMIKA-SAVI Berkonteks Kota Jambi pada Materi Aritmetika Sosial - Harmini, Ani; Asikin, Mohammad; Suyitno, Amin (Edumatica : Jurnal Pendidikan Matematika, 2021)
One strategy to provide innovation in learning is the development of learning media. This study aims to develop the KOMIKA-SAVI media in the context of the city of Jambi on social arithmetic material that is valid and feasible to use. This type of research is Research and Development (RnD) with the ADDIE method. The stages of the ADDIE method consist of analyze, design, develop, implement, and evaluate. The research subjects were 6 students of SMPN 12 Muaro Jambi. Media validation was assessed by media expert lecturers and material experts, as well as teachers. The research instrument was a media and material validation sheet, along with a research trial questionnaire. The results showed that the assessment of the media expert validators with an average (R) = 4.6 and material experts who gave an assessment with an average (R) = 4.5 from the assessment range of 1.00 R < 5.00 which means the media is valid. The results of student respones in the research trial got good media quality with an average positive student respone of 90.67%. So it can be concluded that the media is valid and feasible to use.